Politik Seksual: Fitnah terhadap Organisasi Perempuan Pasca Kemerdekaan di Indonesia - Pohan, Muslim (Madaniyah, 2018)
The study of Gerwani is documented in a book entitled "The Destruction of the Womens Movement in Indonesia, Sexual Politics in Indonesia Post-Fall of the PKI" by Saskia Wieringa. The factor of the massacres and the appearance of Suharto on the stage of power was not only the result of the emergence of sexual metaphors but also the economic turmoil that created a sense of uncertainty in both the army and the Communists (fifth army-the possibility of 21 million peasants and armed laborers escaping AD control). Suharto rose to power by masterminding an unequaled campaign of violence. Not only violence (1965-1966) but also spread slander in the form of allegations of engineering about the occurrence of sexual festivities conducted by members of Gerwani.Â Keywords: Politics, Sexual: Womens Organization, Post-Independence.